Current capacity for diagnosing Alzheimer’s disease in Germany and implications for wait times - Mattke, Soeren; Tang, Yu; Hanson, Mark; von Arnim, Christine A. F.; Frölich, Lutz; Grimmer, Timo; Onur, Oezguer A.; Perneczky, Robert; Teipel, Stefan; Thyrian, Jochen René (Journal of Alzheimer's disease, 2024)
Background: Amyloid-targeting therapies for Alzheimer’s disease (AD) might become available in Germany soon. The combination of a large pool of prevalent cases and a complex diagnostic process to determine eligibility for these treatments is likely t
Gesehen am 18.03.2025